Fermented-milk bacteria: role in intestinal peristalsis regulation - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate a role of fermented-milk bacteria, first of all Lactobacillus and Bifidumbacterium geni, and their metabolic products – short-chain fatty acids in regulation of peristalsis of the bowel.Original positions. In clinical studies the effect of probiotic strains on severity of symptoms of functional bowel disorders is investigated. The greatest attention is given to the effects of Bifidobacterium animalis DN-173 010 strain (commercial name — ActiRegularis). It was found out, that probiotics containing various strains of Lacto- and Bifidobacteria, have mild purging action without the essential undesirable effects and reduce abdominal dyscomfort.Conclusion. The product containing Bifidobacterium animalis DN-173 010 strain (commercial name — ActiRegularis) is effective for medical and preventive purposes for correction of frequency and improvement of stool consistence, decrease of abdominal distention both at functional bowel disorders, and at practically healthy people.